Circulating microRNA as biomarkers of canine mammary carcinoma in dogs. (27th April 2020) - Fish, Eric J.; Martinez‐Romero, Esther Gisela; DeInnocentes, Patricia; Koehler, Jey W.; Prasad, Nripesh; Smith, Annette N.; Bird, Richard Curt
Abstract: Background: Differentiating benign from canine malignant mammary tumors requires invasive surgical biopsy. Circulating microRNAs (miRNA) may represent promising minimally invasive cancer biomarkers in people and animals. Objectives: To evaluate the serum mRNA profile between dogs with and without mammary carcinoma, and to determine if any of these markers have prognostic significance. Animals: Ten healthy client‐owned female dogs (5 intact, 5 spayed) and 10 dogs with histologically confirmed mammary carcinoma were included; 9 were client‐owned, whereas 1 was a research colony dog. Methods: Retrospective study. Serum miRNA was evaluated by RNA deep‐sequencing (RNAseq) and digital droplet PCR (dPCR).Expression of candidate biomarkers miR‐18a, miR‐19b, miR‐29b, miR‐34c, miR‐122, miR‐125a, and miR‐181a was compared with clinical characteristics, including grade, metastasis, and survival. Results: 452 unique serum miRNAs were detected by RNAseq. Sixty‐five individual miRNAs were differentially expressed (>±1.5‐fold) and statistically significant between groups. Serum miR‐19b ( P = .003) and miR‐125a ( P < .001) were significantly higher in the mammary carcinoma group by dPCR. Both had high accuracy based on receiver operator characteristic area under the curve (0.930 for miR‐125a; 0.880 for miR‐19b). Circulating miR‐18a by RNAseq was significantly higher in mammary carcinoma dogs with histologic evidence of lymphatic invasion ( P = 0.03). There was no significant association with any miRNA and survival or inflammatory status. Conclusions and Clinical Importance: Circulating miRNAs are differentially expressed in dogs with mammary carcinoma. Serum miR‐19b and miR‐18a represent candidate biomarkers for diagnosis and prognosis, respectively.